How GPs adapted their practices and organisations at the beginning of COVID-19 outbreak: a French national observational survey. Issue 12 (2nd December 2020) - Saint-Lary, Olivier; Gautier, Sylvain; Le Breton, Julien; Gilberg, Serge; Frappé, Paul; Schuers, Matthieu; Bourgueil, Yann; Renard, Vincent
Abstract : Objectives: To describe how general practitioners (GPs) adapted their practices to secure and maintain access to care in the epidemic phase. A secondary objective was to explore if GPs' individual characteristics and type of practice determined their adaptation. Design: Observational study using an online questionnaire. Organisational changes were measured by a main question and detailed in two specific outcomes. To identify which GPs' characteristics impacted organisational changes, successive multivariate logistic modelling was performed. First, we identified the GPs' characteristics related to organisational changes with a univariate analysis. Then, we tested the adjusted associations between this variable and the following GPs' characteristics: age, gender and type of practice. Setting: The questionnaire was administered online between 14 March and 21 March 2020. Practitioners were recruited by email using the contact lists of different French scientific GP societies. Participants: The target population was GPs currently practising in France (n=46 056). We obtained a total of 7481 responses. Primary and secondary outcome measures: Primary outcome: Proportion of GPs who adapted their practice. Secondary outcome: GPs' characteristics related to organisational changes. Results: Among the 7481 responses, 5425 were complete and were analysed. 3849 GPs (70.9%) changed their activity, 3605 GPs (66.5%) increased remote consultations and 2315 GPs (42.7%) created a specific pathway for probable patients with COVID-19. Among the 3849 GPs (70.9%) who changed their practice, 3306 (91.7%) gave more answers by phone, 996 (27.6%) by email and 1105 (30.7%) increased the use of video consultations. GPs working in multi-professional group practices were more likely to have changed their activity since the beginning of the epidemic wave than GPs working in mono-professional group or single medical practices (adjusted OR: 1.32, 95% CI 1.12 to 1.56, p=0.001). Conclusions: French GPs adapted their practices regarding access to care for patients in the context of the COVID-19 epidemic. This adaptation was higher in multi-professional group practices.